1981
DOI: 10.5834/jdh.31.13
|View full text |Cite
|
Sign up to set email alerts
|

A Field Test on the Caries Preventive Effect of Tea Drinking

Abstract: Abstract:A cup of tea (containing about 0.49 mg F) containing soluble fluoride in the optimum necessary amount was recommended after every school lunch to 298 school children of Suhara in Sumon, Niigata prefecture, for about 250 days from December, 1975 to November, 1976. Increment lesions which appeared at three carious predirective sites, i. e., pits and fissures, proximal, and free gingival smooth surfaces of the children of the test school in the Suhara district were compared to the lesions found at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 8 publications
2
21
0
1
Order By: Relevance
“…A similar finding was made with respect to Bordetella pertussis (16). Other workers (19,30,36) showed that aqueous extracts of green tea inhibited cariogenic streptococci, including Streptococcus mutans; activity against other harmful mouth flora has been reported in the patent literature (45). Tea extracts have been found to be active against Clostridium spp.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…A similar finding was made with respect to Bordetella pertussis (16). Other workers (19,30,36) showed that aqueous extracts of green tea inhibited cariogenic streptococci, including Streptococcus mutans; activity against other harmful mouth flora has been reported in the patent literature (45). Tea extracts have been found to be active against Clostridium spp.…”
supporting
confidence: 65%
“…There is a report in the Japanese-language literature that drinking green tea reduced the incidence of dental caries among schoolchildren (29,30), but the validity of the conclusions is difficult to assess. It has been suggested (13) that this effect was due to an increased intake of fluoride, but this seems unlikely (36); rather, the polyphenol moiety of tea was thought to be responsible.…”
Section: Biological Activities Of Tea Componentsmentioning
confidence: 99%
“…Elvin-Lewis and Steelman [31] found signi®cantly lower DMFT and plaque scores in children who habitually drank one-to-three cups of tea per day than in those whose intake was only one-to-two cups per week (this report is in Abstract form only). The prospective trials by Onisi et al [32,33] showed that Japanese schoolchildren given one cup of green tea (`bancha') daily for 250 days had a 50% reduction in the most common types of carious lesions compared with a control group not given tea, and a reduction in incidence of caries during the ®rst year was maintained thereafter. A recent study in the UK found that 14-year-old children who drank tea (whether with added sugar or not) had a signi®cantly lower DMFT score than coffee drinkers [34].…”
Section: Anti-cariogenic Activity Of Tea In Vivomentioning
confidence: 99%
“…[41][42][43] This effect may be mediated by inhibition of the synthesis of insoluble glucans. 44,45 Epicatechin gallate and epigallocatechin gallate also interfered with the sucrose-dependent adherence of those bacterial cells at concentrations lower than their MIC.…”
Section: H Antibacterial Studiesmentioning
confidence: 99%
“…Significantly lower caries scores were observed in specific pathogen-free rats infected with S. mutans JC-2 and then fed a cariogenic diet and green tea polyphenol mixture. [134][135][136][137] …”
Section: P Dental Cariesmentioning
confidence: 99%